Association of direct bilirubin to total bilirubin ratio with 90-day mortality in patients with acute-on-chronic liver failure - Yuanji Ma; Lingyao Du; Shaoqun Zhou; Lang Bai; Hong Tang (Frontiers in Medicine, 2023)
BackgroundHyperbilirubinemia occurs when the liver fails to process bilirubin properly. A disproportionate increase in direct bilirubin indicates a decreased ability of the hepatocytes to uptake and/or convert bilirubin, which may impact the prognosis of patients with acute-on-chronic liver failure (ACLF). However, the association of direct bilirubin to total bilirubin ratio (DB/TB) with outcomes in patients with ACLF remains unclear.MethodsA retrospective study was conducted in West China Hospital of Sichuan University to assess the association between DB/TB and 90-day mortality in patients with ACLF. The diagnosis of ACLF was based on the Chinese Group on the Study of Severe Hepatitis B (COSSH) ACLF criteria. Ordinal logistic regression models, linear regression models, and Cox proportional hazards models were applied to evaluate the association between DB/TB and hepatic encephalopathy, disease severity, and outcome, respectively.ResultsA total of 258 patients with ACLF were included. The surviving patients were less likely to have liver cirrhosis and comorbidities, and their disease severities were milder than the dead. DB/TB was negatively correlated to cerebral score for hepatic encephalopathy (adjusted odds ratio: 0.01, p = 0.043), and disease severity (adjusted standardized coefficients: −0.42~−0.31, all p < 0.001), respectively. A significant 90-day mortality risk of DB/TB was observed [all adjusted hazard ratio (aHR) < 0.20 and all p ≤ 0.001]. Compared with patients with DB/TB < 0.80, patients with ACLF and DB/TB ≥ 0.80 had much lower 90-day mortality risk (all aHR < 0.75 and all p < 0.01).ConclusionDB/TB could be an independent risk factor to predict the short-term prognosis in patients with ACLF. More attention should be paid to patients with lower DB/TB due to their poorer prognosis and more urgent need for liver transplantation.Clinical trial registration:http://www.chictr.org.cn/showproj.aspx?proj=56960, identifier, ChiCTR2000035013.